Cultural constructions of Turkish-German masculinities in contemporary literature and film - Petersen, Kendall (My University, 2012)
This research sets out to examine the representation of the construction of Turkish-German masculinities and masculine identities, as revealed in the literary and cinematic works of Turkish and Turkish-born writers and filmmakers respectively. To this aim the research will attempt to establish which factors mediate the construction and perpetuation of this hyphenated construct of masculine identity in its capacity to create an identity which, although dependent on the mediating influences of two opposing national identities, remains itself largely intangible and indefinable. The texts examined are Zafer Şenocak’s Die Prärie (1997), and Snow (2004) by Orhan Pamuk. The films are Lola und Bilidikid (1999) directed by Kutlug Ataman, and Gegen die Wand (2004) directed by Fatih Akin. Through an examination of the central characters in these works, it will be established to what extent they could be said to exist as representations or examples of this hyphenated cultural products. These characters will be examined in light of the theory that gender is a process of doing, and not being. Masculinity then, as a performance of gender will be considered in as far as it addresses the performance of a patricular kind of gender identity, namely that of migrant masculinity, in order to establish if there indeed exists an element of credibility to the hyphenated construct of the Turkish-German man, and by extension, to Turkish-German masculinity, as evidenced by the protagonists in the selected works.
Ph.D. University of the Witwatersrand, Faculty of Humanities (German Studies), 2012